Mismatch binding, ADP-ATP exchange and intramolecular signaling during mismatch repair - Hingorani, Manju M. (DNA Repair (Amst), 2015)
The focus of this article is on the DNA binding and ATPase activities of the mismatch repair (MMR) protein, MutS—our current understanding of how this protein uses ATP to fuel its actions on DNA and initiate repair via interactions with MutL, the next protein in the pathway. Structure-function and kinetic studies have yielded detailed views of the MutS mechanism of action in MMR. How MutS and MutL work together after mismatch recognition to enable strand-specific nicking, which leads to strand excision and synthesis, is less clear and remains an active area of investigation.